Two cases of acute respiratory failure following SARS‐CoV‐2 vaccination in post‐COVID‐19 pneumonia. Issue 8 (4th July 2022) - Bando, Tomohiro; Takei, Reoto; Mutoh, Yoshikazu; Sasano, Hajime; Yamano, Yasuhiko; Yokoyama, Toshiki; Matsuda, Toshiaki; Kataoka, Kensuke; Kimura, Tomoki; Kondoh, Yasuhiro
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination is a very effective method of preventing infection and is recommended for people having recovered from coronavirus disease 2019 (COVID‐19). In this novel case report, we describe two patients with post‐COVID‐19 pneumonia who experienced acute respiratory failure and new bilateral ground‐glass opacities several days after receiving SARS‐CoV‐2 vaccination. Both patients were treated with methylprednisolone pulse therapy and recovered from the disease successfully. Indeed, post‐COVID‐19 patients can gain benefits from the vaccine, but vaccination at the early stage of recovery from COVID‐19 might be a risk for certain populations. These cases highlight a potential association between vaccination, interstitial lung disease and worsening of post‐COVID‐19 pneumonia. Further investigation and research examining the relationship between the timing of SARS‐CoV‐2 vaccination and potential risks in post‐COVID‐19 patients is recommended. Abstract : The two cases reported here highlight a potential association between vaccination, interstitial lung disease and worsening of post‐coronavirus disease 2019 (COVID‐19) pneumonia. Further investigation and research examining the relationship between the timing of severe acute respiratory syndrome coronavirus 2 vaccination and potential risks in post‐COVID‐19 patients is recommended.